Facilitating access to sports for people in poverty? A study on local social sports policy - Hanne Vandermeerschen; Marjolein van Poppel; Jeroen Scheerder (Journal of Social Intervention: Theory and Practice, 2016)
SAMENVATTING Mensen in armoede toegang bieden tot sport? Een studie naar lokaal sociaal sportbeleid Onderzoek heeft aangetoond dat armoede een impact heeft op de kansen voor sportdeelname. Mensen in armoede participeren minder in sport in vergelijking met mensen die gemakkelijk(er) rondkomen. Op Vlaams beleidsniveau werden initiatieven genomen om lokale besturen aan te moedigen tot het promoten en faciliteren van sportdeelname voor mensen in armoede. Het is echter nog onduidelijk in welke mate dit ingang vond op lokaal niveau. In deze studie wordt onderzocht in welke mate lokale sportdiensten momenteel initiatieven nemen om sportdeelname bij mensen in armoede te faciliteren, met welke moeilijkheden sportdiensten worden geconfronteerd om dit doel te bereiken, en in welke mate lokaal sociaal sportbeleid tot stand komt door middel van samenwerkingsverbanden tussen de sportsector enerzijds, en de sociale sector anderzijds. De data zijn afkomstig van het Vlaamse Sportdiensten Panel (2014). De resultaten geven onder meer aan dat de publieke sportsector en de sociale sector nog in grote mate twee “gescheiden” werelden zijn. Het blijkt een uitdaging om de afstand tussen beiden te overbruggen. Aanbevelingen voor verder onderzoek en voor de ontwikkeling van een sociaal sportbeleid worden aangereikt. ABSTRACTFacilitating access to sports for people in poverty? A study on local social sports policy Research has shown that living in poverty affects the opportunities for engaging in practicing sports. People in poverty participate less in sports than people who have no (or fewer) difficulties making ends meet. At the Flemish policy level, initiatives have been undertaken to ensure that more local sports authorities promote and facilitate participation in sports for people in poverty. However, it remains unclear how these concerns are being translated at the local level. In this study, we investigate the extent to which local sports authorities are currently undertaking initiatives to facilitate participation in sports for people in poverty, which difficulties local sports authorities encounter in trying to reach this goal, and the extent to which local social sports policy results from partnerships between sports and the social sector. The data used in this study originate from the Flemish Panel study on Local Sports Authorities (2014). The results indicate that the sports sector and the social sector are still, to a large extent, two separate worlds and bridging the gap between them remains a challenge. Suggestions are offered for further research and for the development of social sports policy.